2021
DOI: 10.1111/andr.13063
|View full text |Cite
|
Sign up to set email alerts
|

RUBIC (ReproUnion Biobank and Infertility Cohort): A binational clinical foundation to study risk factors, life course, and treatment of infertility and infertility‐related morbidity

Abstract: Background: Infertility affects 15%-25% of all couples during their reproductive life span. It is a significant societal and public health problem with potential psychological, social, and economic consequences. Furthermore, infertility has been linked to adverse long-term health outcomes. Despite the advanced diagnostic and therapeutic techniques available, approximately 30% of infertile couples do not obtain a live birth after fertility treatment. For these couples, there are no further options to increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…A major limitation of HOMA-IR is that insulin testing is a hard-to-reach and scarce test, especially in low-income populations, and is limited in terms of reproducibility [16]. In this context, the TyG index, based on fasting glucose and triglyceride values, which are low cost and easily accessible biochemistry tests [39,40], has been introduced as an alternative marker of IR. Several studies have shown a positive correlation between HOMA-IR and the TyG index [22] in clinical practice and, of note, some reports have shown that the TyG index is an even better diagnostic tool for IR than the HOMA score in selected patients [16,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation of HOMA-IR is that insulin testing is a hard-to-reach and scarce test, especially in low-income populations, and is limited in terms of reproducibility [16]. In this context, the TyG index, based on fasting glucose and triglyceride values, which are low cost and easily accessible biochemistry tests [39,40], has been introduced as an alternative marker of IR. Several studies have shown a positive correlation between HOMA-IR and the TyG index [22] in clinical practice and, of note, some reports have shown that the TyG index is an even better diagnostic tool for IR than the HOMA score in selected patients [16,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The expertise in various basic and clinical aspects does exist but collaborative projects are usually limited to a few groups or countries. Two good examples are the previously European Union (EU)‐supported European Male Health Study (EMAS) 9 or the currently active ReproUnion Consortium 10 . Several collaborative studies in the frame of the International Male Infertility Genomics Consortium (http://www.imigc.org) testify the importance of joining forces in our field.…”
Section: Figurementioning
confidence: 99%
“…Two good examples are the previously European Union (EU)-supported European Male Health Study (EMAS) 9 or the currently active ReproUnion Consortium. 10 dedicated primarily to couple infertility. However, in most of the European countries, language-specific educational materials for the general public are fragmented or largely missing, and filling this gap will be one of the goals of ANDRONET.…”
Section: S U P P L E M E N T a R T I C L E Andronet: A New European N...mentioning
confidence: 99%